Methods for enhancing carbon product performance in elastomers
By treating pyrolytic carbon with water and additional fillers to enhance particle size distribution and dispersion, the method addresses the poor performance of recycled carbon in elastomers, achieving comparable mechanical properties and fatigue resistance to carbon black.
Patent Information
- Application Number
- JP2024537109
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-12-21
- Filing Date
- 2022-12-20
- Publication Date
- 2025-01-09
- Estimated Expiration
- 2042-12-20
AI Technical Summary
Recycled carbon from pyrolysis of rubber products, such as tire components, does not perform as effectively as carbon black in reinforcing elastomers due to poor mechanical properties and fatigue resistance, limiting its use in rubber composites.
A method involving the treatment of pyrolytic carbon with water to form a slurry, followed by milling and blending with additional fillers, then pelletizing or spray drying to produce a carbon product with improved particle size distribution and dispersion, enhancing its performance in elastomer composites.
The treated recycled carbon exhibits improved mechanical properties and fatigue resistance, comparable to carbon black, when incorporated into elastomer composites, thereby improving the performance of rubber products.
Smart Images

Figure 2025500320000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an improved method for processing recycled carbon black. [Background technology]
[0002] Frequently, used automobile tires are processed and reused in a wide range of end uses, from playground equipment to concrete. However, to reduce the amount of new material required to manufacture new tires, it is desirable to recycle components of tires to obtain materials that can be combined with first-use materials. Tires can be processed via pyrolysis, i.e., heating in the absence of oxygen, to convert elastomers to lower molecular weight hydrocarbons and recover carbonaceous powders. However, the resulting powders are not equivalent to carbon black as a rubber reinforcement agent. Even in combination with carbon black, they result in inferior fatigue performance and other mechanical properties. Therefore, it is desirable to improve the performance of particulate carbon recovered by pyrolysis from tires and other sources to reduce the environmental impact of waste tires. Summary of the Invention
[0003] As used herein, "char" means the solid material resulting from the thermal decomposition of rubber products.
[0004] As used herein, "dry reground carbon" is pyrolytic carbon that is substantially free of contaminants visible to the naked eye and that has been ground without the use of water, and optionally pelletized.
[0005] As used herein, "carbon black" means carbon-containing particles of elemental carbon organized into aggregates and agglomerates obtained by the partial combustion or pyrolysis of hydrocarbons.
[0006] As used herein, "raw reclaimed carbon" is a solid material resulting from the pyrolysis of rubber products containing any amount of carbonaceous particulate filler, including but not limited to carbon black.
[0007] As used herein, "processed regenerated carbon" means raw regenerated carbon that has been treated to remove at least one macroscopic contaminant, such as fabric or wire.
[0008] As used herein, "pyrolytic carbon" includes char, raw reclaimed carbon, processed reclaimed carbon, and dried ground reclaimed carbon.
[0009] As used herein, "regrinded carbon" or "ground rC" is pyrolytic carbon that is substantially free of macroscopic contaminants and has been ground up.
[0010] As used herein, "reclaimed carbon" is raw reclaimed carbon that has been treated to remove macroscopic contaminants and, optionally, further ground. Thus, processed reclaimed carbon, reground carbon, dry reclaimed carbon, and wet reclaimed carbon all fall within the definition of reclaimed carbon.
[0011] As used herein, "wet reground carbon" is pyrolytic carbon that is substantially free of contaminants visible to the naked eye and that has been ground in the presence of at least 50% by weight water, preferably 65-99% water, based on the total weight of the material being ground.
[0012] In one embodiment, a method of treating particulate carbon includes combining pyrolytic carbon with water to form a mixture to form an initial slurry having a solids content of 1-35% by weight, and grinding the pyrolytic carbon to form a grinding slurry of wet regrind carbon and water. The volume weighted particle size distribution curve of the wet regrind carbon measured via scanning electron microscopy has one or more of a D50 of 2700 nm or less and 15% or less of particles having a particle size greater than 5 microns, e.g., a D50 of 1000 nm to 2700 nm or 1200 nm to 2500 nm. Alternatively, or in addition, the wet regrind carbon may have a D75 of 2500 nm to 3300 nm, e.g., 1700 nm to 3000 nm. Alternatively, or in addition, 3% to 10% of the wet regrind carbon particles have a particle size greater than 5 microns. Alternatively, or in addition, 65% or less of the particles, e.g., 25% to 60%, may have a particle size greater than 2 microns.
[0013] The method may further include removing visible contaminants from the initial slurry, which may optionally have a solids content of up to 25% by weight. The combining may further include combining at least one auxiliary filler with water to form the initial slurry. The auxiliary filler may be selected from the group consisting of carbon black, silicon-treated carbon black, silica-coated carbon black, precipitated silica, hydrothermal carbon, artificial polysaccharides, graphene, graphene oxide, reduced graphene oxide, nanocellulose, lignin, clay, nanoclay, metal oxides, metal carbonates, single-walled carbon nanotubes, multi-walled carbon nanotubes, carbon nanostructures, carbon black-coated particles, and mixtures of two or more thereof. The grinding may be performed using at least one device selected from a cutter mixer, a ball mill, a media mill, a homogenizer, an attritor, a horizontal bead mill, a rotor-stator mill, and a colloid mill.
[0014] The method may further include adding at least one additional filler selected from carbon black, silicon treated carbon black, silica coated carbon black, coated carbon black particles, and precipitated silica to the milled slurry to provide a solids content of the resulting wet blended carbon mixture of 25-70% by weight. Adding may include adding an aqueous slurry containing the at least one additional filler, adding additional water to the milled slurry, or both. The method may further include pelletizing the wet blended carbon mixture to form pellets, or spray drying the wet blended carbon mixture, and optionally drying the pellets.
[0015] The water may be a continuous flow of water, the milled slurry may be a continuous flow of milled slurry, and combining may include metering pyrolytic carbon into the continuous flow of water. Combining may further include metering at least one auxiliary filler into the continuous flow of water. The auxiliary filler may be selected from the group consisting of carbon black, silicon treated carbon black, silica coated carbon black, precipitated silica, hydrothermal carbon, artificial polysaccharides, graphene, graphene oxide, reduced graphene oxide, nanocellulose, lignin, clay, nanoclay, metal oxides, metal carbonates, single walled carbon nanotubes, multi walled carbon nanotubes, carbon nanostructures, carbon black coated particles, and mixtures of two or more thereof. The method may further include metering at least one additional filler selected from carbon black, silicon treated carbon black, silica coated carbon black, carbon black coated particles, and precipitated silica into the continuous flow of milled slurry to provide a solids content of the resulting continuous flow of wet blended carbon mixture of 25-70% by weight or 1-25% by weight. Metering can include metering an aqueous slurry of additional filler into the continuous flow of the milled slurry, metering additional water into the continuous flow of the milled slurry, or both.
[0016] In any of these embodiments, the method may further include granulating the wet blended carbon mixture, for example, by pelletizing the wet blended carbon mixture to form pellets or by spray drying the wet blended carbon mixture. The pellets may be dried. The milled slurry may be spray dried or otherwise granulated to its solids. For example, the milled slurry may be dewatered to a predetermined moisture level and then pelletized.
[0017] In another embodiment, the present invention comprises pellets produced using any combination or subcombination of the above process steps.
[0018] In another embodiment, the particulate filler comprises at least 10% by weight (dry basis), e.g., 10-100%, 10-90%, 15-80%, 20-60%, or 30-50% by weight of recycled carbon. The volume-weighted particle size distribution of the recycled carbon, measured via scanning electron microscopy, has one or more particles with a D50 of 2700 nm or less and 15% or less having a particle size greater than 5 microns. For example, the recycled carbon may have a D50 of 1000 nm to 2700 nm or 1200 nm to 2500 nm. Alternatively, or in addition, the recycled carbon may have a D75 of 2500 nm to 3300 nm, e.g., 1700 nm to 3000 nm. Alternatively, or in addition, 3% to 10% of the recycled carbon may have a particle size greater than 5 microns. Alternatively, or in addition, up to 65% of the regenerated carbon may have a particle size greater than 2 microns, for example between 25% and 60%.
[0019] In any of these embodiments, the particulate filler may further comprise one or more auxiliary fillers selected from carbon black, silicon-treated carbon black, silica-coated carbon black, precipitated silica, hydrothermal carbon, artificial polysaccharides, graphene, graphene oxide, reduced graphene oxide, nanocellulose, lignin, clay, nanoclay, metal oxides, metal carbonates, single-walled carbon nanotubes, multi-walled carbon nanotubes, carbon nanostructures, and carbon black-coated particles. The particulate filler may have a moisture content of 15 to 80% by weight, for example 40 to 60% by weight.
[0020] The particulate filler may be in the form of pellets. The pellets may contain 15-80% water, for example 40-60% water, or may contain 3% water or less, and / or may consist essentially of the particulate filler, any water, and any binder. The pellets may contain the particulate filler according to any of these embodiments, and at least one additional filler selected from carbon black, silicon-treated carbon black, silica-coated carbon black, carbon black-coated particles, and precipitated silica.
[0021] In any of these embodiments, the regenerated carbon may be wet-grind regenerated carbon.
[0022] In another embodiment, the elastomer composite comprises a mixture of an elastomer and 30-90 phr, e.g., 30-70 phr, 35-60 phr, or 40-55 phr, of a particulate filler. The particulate filler comprises at least 10 wt. % recycled carbon, e.g., 10-100 wt. %, 10-90 wt. %, 15-80 wt. %, 20-60 wt. %, or 30-50 wt. % recycled carbon. The recycled carbon, in particulate form, i.e., before being mixed with the elastomer, has one or more of a D50 (volume weighted) of 2700 nm or less and 15% or less (volume weighted) having a particle size greater than 5 microns, as measured by scanning electron microscopy. For example, the recycled carbon may have a D50 of 1000 nm to 2700 nm or 1200 nm to 2500 nm. Alternatively, or in addition, the regenerated carbon may have a D75 of 2500 nm to 3300 nm, e.g., 1700 nm to 3000 nm. Alternatively, or in addition, 3% to 10% of the regenerated carbon may have a particle size greater than 5 microns. Alternatively, or in addition, up to 65% of the regenerated carbon, e.g., 25% to 60%, may have a particle size greater than 2 microns. The particulate filler may further comprise one or more of carbon black, silicon-treated carbon black, silica-coated carbon black, precipitated silica, hydrothermal carbon, artificial polysaccharides, graphene, graphene oxide, reduced graphene oxide, nanocellulose, lignin, clay, nanoclay, metal oxides, metal carbonates, single-walled carbon nanotubes, multi-walled carbon nanotubes, carbon nanostructures, and carbon black-coated particles.
[0023] In any of these embodiments, the elastomer may be selected from natural rubber, functionalized natural rubber, styrene-butadiene rubber, functionalized styrene-butadiene rubber, polybutadiene rubber, functionalized polybutadiene rubber, polyisoprene rubber, ethylene-propylene copolymers, isobutylene based rubber, polychloroprene rubber, nitrile rubber, hydrogenated nitrile rubber, polysulfide rubber, polyacrylate elastomers, fluoroelastomers, perfluoroelastomers, and blends thereof.
[0024] In any of these embodiments, the elastomer composite may exhibit a macrodispersity of up to 0.03x+4.4, e.g., from 0.03x to 0.03x+4.4, where x is the percentage of recycled carbon in the particulate filler and the macrodispersion is the area percentage of undispersed filler particles greater than 5 μm as determined by optical microscopy in reflectance mode. When the particulate fillers are recycled carbon and carbon black, the elastomer composite may exhibit a macrodispersity of up to 1.9ln(x)+1.2, e.g., from 1.9ln(x)-3.2 to 1.9ln(x)+0.2.
[0025] In any of these embodiments, the regenerated carbon may be wet-grind regenerated carbon.
[0026] In any of these embodiments, the elastomer composite may be a vulcanized elastomer composite. The tire tread may include a vulcanizate of a mixture of the elastomer composite and a curative package. Alternatively, or in addition, the article may include a vulcanizate of a mixture of the elastomer composite and a curative package. The article may be incorporated into a pneumatic tire, a non-pneumatic tire, or a solid tire. The article may be selected from a tire tread, an undertread, an innerliner, a sidewall, a sidewall insert, a wire skim, and a cushion gum for a retread tire. The articles may be selected from hoses, linings, liners, seals, gaskets, vibration isolation articles, trucks, track pads for truck propelled vehicle equipment, engine mounts, seismic stabilization devices, screens for mining equipment, linings for mining equipment, conveyor belts, chute liners, slurry pump liners, mud pump impellers, valve seats, valve bodies, piston hubs, piston rods, plungers, slurry mixing impellers and slurry pump impellers, crusher liners, cyclones and hydrocyclones, expansion joints, linings for dredge pumps and outboard pumps for marine equipment, shaft seals for marine, oil, aerospace, and other applications, propeller shafts, pipe linings, engine mounts, bushings, weatherstripping, windshield wipers, automotive parts, seals, gaskets, housings, wheel elements, and truck elements.
[0027] Alternatively, or in addition, a vulcanizate of the elastomer composite mixture with the curative package has fatigue properties equivalent to or at least 90% of a vulcanizate produced via the same process and same composition, but with ASTM N550 carbon black instead of recycled carbon. The vulcanizate may exhibit a macrodispersity of up to 0.03x+4.4, e.g., 0.03x to 0.03x+4.4, where x is the percentage of recycled carbon in the particulate filler, and the macrodispersion is the area percentage of undispersed filler particles greater than 5 μm as determined by optical microscopy in reflectance mode. When the particulate filler is recycled carbon and carbon black, the vulcanizate may exhibit a macrodispersity of up to 1.9ln(x)+0.2, e.g., 1.9ln(x)-3.2 to 1.9ln(x)+0.2.
[0028] In another embodiment, the elastomer composite comprises a mixture of an elastomer and 30 to 90 phr of particulate filler. In certain embodiments, the particulate filler comprises at least 10 wt. % recycled carbon, and the elastomer composite exhibits a macrodispersion of at most 0.03x+4.4, e.g., 0.03x to 0.03x+4.4, where x is the percentage of recycled carbon in the particulate filler, and the macrodispersion is the area percentage of undispersed filler particles greater than 5 μm as determined by optical microscopy in reflectance mode. When the particulate filler comprises at least 10 wt. % (dry basis) recycled carbon with the balance being carbon black, the macrodispersion is at most 1.9ln(x)+1.2, e.g., 1.9ln(x)-3.2 to 1.9ln(x)+0.2. In any of these embodiments, the elastomer composite may be vulcanized and / or the recycled carbon may be wet-ground regenerated carbon. The regenerated carbon may have one or more particles with a D50 (volume weighted) of 2700 nm or less and 15% (volume weighted) or less having a particle size greater than 5 microns as measured by scanning electron microscopy. For example, the regenerated carbon may have a D50 of 1000 nm to 2700 nm or 1200 nm to 2500 nm. Alternatively, or in addition, the regenerated carbon may have a D75 of 2500 nm to 3300 nm, e.g., 1700 nm to 3000 nm. Alternatively, or in addition, 3% to 10% of the regenerated carbon may have a particle size greater than 5 microns. Alternatively, or in addition, 65% or less of the regenerated carbon, e.g., 25% to 60%, may have a particle size greater than 2 microns.
[0029] It is to be understood that both the foregoing general description and the following detailed description are exemplary and explanatory only and are intended to provide further explanation of the invention as claimed. [Brief description of the drawings]
[0030] The invention will now be explained with reference to the several figures of the drawing.
[0031] [Figure 1]FIG. 1 shows the particle size distribution of raw char (dash-dotted line, CBP Cyprus) that has been jet milled (dashed line) or processed according to an exemplary embodiment (solid line). [Diagram 2] FIG. 2 shows the particle size distribution of samples of char processed according to an exemplary embodiment (dashed line - CBP Cyprus, dashed line - Polimix Ambiental) and Polymix 300 processed regenerated carbon (solid line). [Diagram 3] FIG. 3 shows the particle size distribution of jet milled samples of char (dashed line - CBP Cyprus, dashed line - Polimix Ambiental) and Polymix 300 processed regenerated carbon (solid line). [Figure 4] Figure 4 shows undispersed agglomerates with diameters greater than 5 microns in filled elastomer composites as a function of the percentage of recycled carbon in the filler. The triangles represent comparative samples and the circles represent samples prepared according to an embodiment of the invention. The sample with 26.9% recycled carbon uses a blend of recycled carbon and precipitated silica as the filler, while the remaining blend includes carbon black. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0032] In one embodiment, a method of treating particulate carbon includes combining pyrolytic carbon with water to form a mixture to form an initial slurry having a solids content of 1-35% by weight, and grinding the pyrolytic carbon to form a grinding slurry of wet reground carbon and water. The volume weighted particle size distribution of the grinding slurry, measured via scanning electron microscopy, has one or more of a D50 of 2700 nm or less and 15% or less of particles having a particle size greater than 5 microns, e.g., a D50 of 1000 nm to 2700 nm or 1200 nm to 2500 nm. Alternatively, or in addition, the grinding slurry may have a D75 of 2500 nm to 3300 nm, e.g., 1700 nm to 3000 nm. Alternatively, or in addition, 3% to 10% of the particles have a particle size greater than 5 microns. Alternatively, or in addition, 65% or less of the particles, e.g., 25% to 60%, may have a particle size greater than 2 microns.
[0033] The pyrolytic carbon may include one or more of raw reclaimed carbon, processed reclaimed carbon, and dried ground reclaimed carbon. Preferably, the pyrolytic carbon is derived from a rubber product that was originally made with carbon black. Pyrolysis may be carried out by any method known to those skilled in the art. Exemplary methods include, but are not limited to, those found in U.S. Pat. No. 8,350,105 and U.S. Patent Application Publication No. 2018 / 0320082, the entire contents of both of which are incorporated herein by reference. The pyrolytic carbon is combined with water to form an initial slurry having a solids concentration of 1-35% by weight, e.g., 5-30% by weight, 7-25% by weight, 10-20% by weight, or 15-25% by weight. The concentration is preferably adjusted to the concentration required for downstream processes, including grinding and optional pelletization.
[0034] The pyrolytic carbon may be treated to remove macroscopic contaminants. For example, magnetic separation techniques known to those skilled in the art may be used to remove wires and other macroscopic metallic contaminants. Filters or screens may be used to remove fabrics and other non-magnetic macroscopic contaminants. The pyrolytic carbon may be treated before being combined with water to form the initial slurry, and / or the initial slurry may be treated to remove macroscopic contaminants.
[0035] Alternatively, or in addition, the pyrolytic carbon may be treated to remove ash, for example, by washing the pyrolytic carbon with an acid or by using an ion exchanger. Exemplary methods are described in U.S. Patent Application Publication No. 2015,0307714, Chinese Patent Application Publication No. 101,357,758, and International Publication No. WO 2021 / 005124, the entire contents of which are incorporated herein by reference.
[0036] In some embodiments, the method is continuous. In these embodiments, pyrolytic carbon is continuously metered into a continuous flow of water to form a continuous flow of initial slurry. The continuous flow of initial slurry may be treated using techniques known to those skilled in the art to remove contaminants visible to the naked eye.
[0037] The initial slurry, following any processing, is milled. Any technique known to those skilled in the art for milling or grinding particulate slurries may be used. Exemplary equipment includes cutter mixers, ball mills, media mills, homogenizers, attritors, horizontal bead mills, rotor stator mills, colloid mills, and other equipment known to those skilled in the art. Milling may convert the pyrolytic carbon to a wet reground carbon having a volume weighted particle size distribution, measured via scanning electron microscopy, characterized by one or both of a D50 of 2700 nm or less and 15% or less particles having a particle size greater than 5 microns. For example, the D50 may be 1000 nm to 2700 nm or 1200 nm to 2500 nm. Alternatively, or in addition, the milled slurry may have a D75 of 2500 nm to 3300 nm, e.g., 1700 nm to 3000 nm. Alternatively, or in addition, 3% to 10% of the particles have a particle size greater than 5 microns. Alternatively, or in addition, up to 65% of the particles, e.g., 25% to 60%, may have a particle size greater than 2 microns. Without being bound to any particular theory, it is believed that the performance of vulcanized elastomeric composites produced with dry reground carbon is degraded due to the presence of large weak agglomerates that are poorly dispersed in the elastomer. The methods provided herein more effectively reduce the weak agglomerate size, thereby improving the dispersion of the filler in the elastomeric matrix and improving the performance of the resulting vulcanized elastomeric composites. The improved mechanical performance may be reflected in fatigue performance, tensile performance, tear performance, cut / chip performance, or other properties typically measured on elastomeric composites.
[0038] The particle size distribution may be measured using any suitable method known to those skilled in the art, for example laser diffraction. Preferably, the particle size distribution is measured using scanning electron microscopy, for example the scanning electron microscopy method described in more detail in the Examples. Briefly, the particles are dispersed at a concentration of 0.2% by weight in water with 600 ppm Triton® X 100 surfactant at low speed and then stirred for 24 hours. The dispersion is diluted to an appropriate concentration, filtered onto a membrane filter, dried, sputter coated with a conductive material, and imaged. Imaging is performed at high and low magnifications to provide sufficient resolution to capture small particles while efficiently imaging larger particles. Images are processed to minimize non-uniform image background, enhance particle contrast, and reduce image noise while preserving particle edges. The particle size distribution is measured using a Dcirc=2(area of projected image / π) over at least 50,000 particles, typically 50,000 to 200,000 particles at each magnification. 1 / 2 is determined by measuring
[0039] The initial slurry may also contain one or more auxiliary fillers that may also benefit from being co-ground with the pyrolytic carbon. Any particulate filler that provides reinforcement or other beneficial properties to the rubber may be used. Exemplary auxiliary fillers include carbon black, silicon-treated carbon black, silica-coated carbon black, precipitated silica, hydrothermal carbon (i.e., carbonaceous materials produced by hydrothermal carbonization of lignin or other biomass, such as those described in U.S. Patent Application Publication Nos. 2020 / 181370 and 2020 / 190270, the contents of both of which are incorporated herein by reference), and the like. As well as graphene, graphene oxide, reduced graphene oxide, nanocellulose, lignin, clay, nanoclay, metal oxides, metal carbonates, single-walled carbon nanotubes, multi-walled carbon nanotubes, carbon nanostructures such as those described in US Patent Publication No. 2014 / 0093728 (the entire contents of which are incorporated herein by reference), and carbon black coated particles such as those described in US Patent No. 10,519,298 (the entire contents of which are incorporated herein by reference). Preferably, contaminants visible to the naked eye are removed from the pyrolytic carbon in either a dry or slurried state before combining the pyrolytic carbon with one or more auxiliary fillers. The auxiliary fillers can be combined with the pyrolytic carbon in a dry state or separately charged into the water before, after, or simultaneously with the pyrolytic carbon to form the initial slurry. To avoid possible separation in the dry mixture of pyrolytic carbon and auxiliary fillers, the auxiliary fillers are preferably charged directly into the water or initial slurry, separate from the pyrolytic carbon. The ratio of pyrolytic carbon and supplemental filler in the initial slurry can be in any range suitable for the desired end use and suitable for maintaining an acceptable viscosity of the initial slurry so that it can be milled.In a continuous process, the auxiliary filler may be metered into the initial slurry as a powder or as an aqueous slurry of the auxiliary filler (or two or more slurries if two or more auxiliary fillers are used) or continuously into a continuous flow of water. Those skilled in the art will recognize that the appropriate concentration for grinding depends on the nature of the auxiliary filler. For example, carbon nanotubes increase the slurry viscosity at very low concentrations, but higher concentrations of precipitated silica may not increase the viscosity dramatically.
[0040] Additional fillers may also be added to the milled slurry. Such additional fillers preferably do not require additional milling. Exemplary additional fillers for addition to the milled slurry include, but are not limited to, carbon black, silica-coated carbon black, silica-treated carbon black, precipitated silica, carbon black-coated particles such as those described in U.S. Pat. No. 10,519,298, and mixtures of two or more thereof. Depending on the solids concentration of the milled slurry, it may also be desirable to add water with the additional filler to adjust the solids concentration of the resulting wet blended carbon mixture. Alternatively, or in addition, the additional filler may be added to the milled slurry as an aqueous slurry. In a continuous process, the additional filler may be metered continuously into the initial slurry or into a continuous flow of water, either as a powder or as an aqueous slurry of the additional filler. The total filler concentration may be such that the wet blended carbon mixture can be easily formed into pellets or spray dried. To form pellets, the additional filler and optional water added to the milled slurry can provide a solids content of the resulting wet blended carbon mixture of 25-70% by weight, e.g., 30-65% by weight, 35-60% by weight, or 40-50% by weight. For spray drying, the additional filler and optional water added to the milled slurry can provide a solids content of the resulting wet blended carbon mixture of 1-30% by weight, e.g., 1-10% by weight, 5-15% by weight, or 8-25% by weight. For spray drying, it may be desirable to omit the additional filler. Those skilled in the art will recognize how to adjust the total filler concentration to prepare the optimum concentration for the desired pellet or spray drying in conventional equipment. The filler added to the milled slurry can be the same or different from any filler added to the initial slurry.
[0041] Carbon blacks for use in any of the embodiments herein include, but are not limited to, ASTM N100 series to N900 series carbon blacks, such as N100 series carbon blacks, N200 series carbon blacks, N300 series carbon blacks, N500 series carbon blacks, N600 series carbon blacks, N700 series carbon blacks, N800 series carbon blacks, or N900 series carbon blacks. Carbon blacks available from Cabot Corporation sold under the trademarks Regal™, Black Pearls™, Spheron™, Sterling™, and Vulcan™, carbon blacks available from Birla Carbon (Columbian Chemicals) sold under the trademarks Raven™, Statex™, Furnex™, and Neotex™ and CD and HV lines, carbon blacks available from Orion Engineered Carbons sold under the trademarks Corax™, Durax™, Ecorax™, and Purex™ and CK lines and other carbon blacks, as well as other fillers suitable for use in rubber or tire applications, may also be utilized for use with the various embodiments. Carbon blacks may be chemically functionalized. Suitable chemically functionalized carbon blacks include those disclosed in WO 96 / 18688 and U.S. Patent Application Publication No. 2013 / 0165560, the disclosures of which are incorporated herein by reference.
[0042] Carbon black should be at least about 15m 2 / g, for example, about 15m 2 / g ~ approx. 240m 2 / g, for example, about 35m 2 / g ~ approx. 230m 2 / g, approx. 50m 2 / g~about 200m 2 / g, approx. 60m 2 / g to about 180m 2 / g, about 100m2 / g to about 200m 2 / g statistical thickness specific surface area (STSA, ASTM standard D6556).
[0043] Carbon black having any of the above specific surface areas may further have a structure in which the oil absorption of compressed carbon black (COAN, ASTM D3493) is about 50 to about 115 mL / 100 g, for example, about 65 to about 75 mL / 100 g, about 60 to about 95 mL / 100 g, about 75 to about 85 mL / 100 g, about 85 to about 95 mL / 100 g, about 95 to about 105 mL / 100 g, or about 105 to about 115 mL / 100 g.
[0044] Mixtures of any of these carbon blacks can be used.
[0045] The materials described herein as silicon-treated carbon blacks are not limited to coated or otherwise modified carbon black aggregates. They may also be different types of aggregates having two phases. One phase is carbon, which still exists as graphitic crystallites and / or amorphous carbon, while the second phase is silica (and possibly other silicon-containing species). Thus, the silicon-containing species phase of silicon-treated carbon black is an inherent part of the aggregate and is distributed throughout at least a portion of the aggregate. Various silicon-treated blacks are available from Cabot Corporation under the name Ecoblack™ and are described in more detail in U.S. Pat. No. 6,028,137. It is understood that multi-layer aggregates are quite different from the silica-coated carbon blacks described above, which consist of preformed single-layer carbon black aggregates with silicon-containing species deposited on their surfaces. Such carbon blacks may be surface treated to place silica functionality on the surface of the carbon black aggregates, as described, for example, in U.S. Pat. Nos. 6,929,783, 6,541,113, and 5,679,728.
[0046] In any of the embodiments herein, suitable precipitated silicas for use include both highly dispersible granulated (HDS) and non-HDS precipitated silicas. Precipitated silicas may be chemically treated to include functional groups such as coupling agents bonded (attached (e.g., chemically attached) or adsorbed (e.g., absorbed)) to the silica surface. Examples of suitable grades of HDS include Perkasil™ GT 3000GRAN silica from WR Grace & Co, Ultrasil™ 7000 silica from Evonik Industries, Zeosil™ 1165 MP and 1115 MP silica from Solvay SA, Hi-Sil™ EZ 160G silica from PPG Industries Inc., and Zeopol™ 8741 or 8745 silica from Evonik Industries. Examples of suitable grades of conventional (non-HDS) precipitated silica include Perkasil® KS 408 silica from WR Grace & Co, Zeosil® 175GR silica from Solvay SA, Ultrasil® VN3 silica from Evonik Industries, and Hi-Sil® 243 silica from PPG Industries, Inc. Examples of suitable grades of hydrophobic precipitated silica include Agilon® 400, 454, or 458 silica from PPG Industries, Inc., and Coupsil® silica from Evonik Industries, such as Coupsil® 6109 silica.
[0047] The wet blended carbon mixture may be densified, e.g., granulated or pelletized. Any densification or pelletization method known to those skilled in the art may be used. For example, the method described in Glaxner, U.S. Pat. No. 2,065,371 may be used. Generally, the wet blended carbon mixture may be formed into beads, which may then be optionally dried to reduce the moisture content to up to 1% to form blended carbon pellets. In addition to the water already present in the wet blended carbon mixture, a wide variety of binding additives are known to be useful in the wet pelletization process to further improve the handling characteristics of the resulting pellets. Such additives include, but are not limited to, hygroscopic organic liquids such as ethylene glycol, carbohydrates (e.g., sugars, molasses, soluble starches, sugars, lignin derivatives), rosin, sulfonate and sulfate anionic surfactants, fatty amine ethoxylate nonionic surfactants, sodium lignin sulfonate, silanes, sucrose, alkyl succinimides, alkylated succinic acid esters, and polyethylene oxide-co-polydimethyl siloxane surfactants. Alternatively, or in addition, the pellets need not be dried but may be used in a wet state, in which case no binder need be used. For example, the wet pellets may have a moisture content of 15-80% by weight, e.g., 40-60% by weight.
[0048] The particulate filler obtained in the form of wet or dry pellets or some other form (e.g., a slurry prior to pelletization or other drying process) may comprise, on a dry basis, 2-100% by weight, e.g., 5-98% by weight or 8-90% by weight, 10-60% by weight, 15-50% by weight, 10-100% by weight, 15-60% by weight, 10-90% by weight, 15-80% by weight, 20-60% by weight, or 30-50% by weight, or 20-50% by weight of regenerated carbon, preferably wet ground regenerated carbon. and the remainder being fillers other than the recycled carbon, such as the additional and / or auxiliary fillers listed above, such as one or more of carbon black, silicon-treated carbon black, silica-coated carbon black, precipitated silica, hydrothermal carbon, artificial polysaccharides, graphene, graphene oxide, reduced graphene oxide, nanocellulose, lignin, clay, nanoclay, metal oxides, metal carbonates, single-walled carbon nanotubes, multi-walled carbon nanotubes, carbon nanostructures, and carbon black coated particles. The volume-weighted particle size distribution of the recycled carbon and / or the overall particulate filler (i.e., the mixture of recycled carbon and other fillers), as measured via scanning electron microscopy, may have one or more of a D50 of 2700 nm or less and 15% or less of particles having a particle size greater than 5 microns, e.g., a D50 of 1000 nm to 2700 nm or 1200 nm to 2500 nm. Alternatively, or in addition, the recycled carbon and / or overall particulate filler may have a D75 of 2500nm to 3300nm, for example 1700nm to 3000nm. Alternatively, or in addition, 3% to 10% of the recycled carbon and / or overall particulate filler may have a particle size greater than 5 microns. Alternatively, or in addition, up to 65% of the recycled carbon and / or overall particulate filler may have a particle size greater than 2 microns, for example 25% to 60%. As above, the pellets may also contain a binder. In all these embodiments, the recycled carbon is preferably wet-ground regenerated carbon.
[0049] Alternatively, or in addition, the wet blended carbon mixture may be spray dried using any spray drying equipment known to those skilled in the art. The resulting spray dried particles may be 2-100% regenerated carbon, e.g., 5-98% or 8-90%, 10-60%, 15-50%, 10-100%, 15-60%, 10-90%, 15-80%, 20-60%, or 30-50%, or 20-50% regenerated carbon, preferably wet ground regenerated carbon, and 0-98% by weight, e.g., 2% to 95% by weight, e.g., 10% to 92% by weight, 40% to 90% by weight, or 50% to 80% or 85% by weight of carbon black, silica coated carbon black, silica treated carbon black, precipitated silica, carbon black coated particles, etc. and a mixture of two or more thereof, and 0 to 98% by weight, for example, 2 to 95% by weight, for example, 10 to 92% by weight, 40 to 90% by weight, or 50 to 80% by weight or 85% by weight of one or more auxiliary fillers selected from carbon black, silicon-treated carbon black, silica-coated carbon black, precipitated silica, hydrothermal carbon, artificial polysaccharides, graphene, graphene oxide, reduced graphene oxide, nanocellulose, lignin, clay, nanoclay, metal oxides, metal carbonates, single-walled carbon nanotubes, multi-walled carbon nanotubes, carbon nanostructures, and carbon black-coated particles.
[0050] The wet pellets, dry pellets, and / or spray-dried particles according to various embodiments herein can be combined with an elastomer to form an elastomer composite. The resulting elastomer composite can include 30-90 phr of particulate filler, for example, 30-70, 35-60, or 40-55 phr of particulate filler. The particulate filler can include 2-100 wt. % recycled carbon, for example, 5-98 wt. % or 8-90 wt. %, preferably 10-100 wt. %, 10-90 wt. %, 15-80 wt. %, 20-60 wt. %, or 30-50 wt. % recycled carbon, preferably wet-ground regenerated carbon, and exhibit a volume-weighted particle size distribution, as measured via scanning electron microscopy, having one or both of a D50 of 2700 nm or less and 15% of particles having a particle size greater than 5 microns. For example, either the recycled carbon or the overall particulate filler, or both, may exhibit a D50 of 1000 nm to 2700 nm or 1200 nm to 2500 nm. Alternatively, or in addition, the recycled carbon, the overall particulate filler, or both, may have a D75 of 2500 nm to 3300 nm, e.g., 1700 nm to 3000 nm. Alternatively, or in addition, 3% to 10% of the recycled carbon, the particulate filler, or both, may have a particle size greater than 5 microns. Alternatively, or in addition, up to 65%, e.g., 25% to 60%, of the recycled carbon or the overall particulate filler may have a particle size greater than 2 microns. In all of these embodiments, the recycled carbon is preferably wet-ground regenerated carbon. Both natural rubber and synthetic elastomers of any grade may be used. Blends of elastomers may also be used. For example, the wet pellets, dry pellets and / or spray-dried particles may be combined with an elastomer to form a masterbatch, and the masterbatch may then be combined with additional elastomers of the same or different composition. Alternatively, or in addition, two or more elastomers may be blended prior to mixing with the pellets. Alternatively, or in addition, the elastomer composite may also contain one or more fillers, including any of the particulate fillers listed elsewhere herein, except for recycled carbon, and any other fillers known to one of ordinary skill in the art for use in elastomer composites.Such fillers may be in a mixture with the reground carbon, in the pellets, or may be added to the elastomer separately from either the wet pellets, dry pellets, and / or spray-dried particles according to various aspects herein.
[0051] The elastomer composite can exhibit a macrodispersion of up to 0.03x+4.4, e.g., 0.03x to 0.03x+4.4, in particular when the filler comprises 10-100 wt.%, e.g., 10-90 wt.%, 15-80 wt.%, 20-60 wt.%, or 30-50 wt.% recycled carbon, preferably wet-ground regenerated carbon, where x is the percentage of wet-ground regenerated carbon in the particulate filler, and the macrodispersion is the area percentage of undispersed filler particles larger than 5 μm (% undispersed area) determined by optical microscopy in reflectance mode after the sample is cut to reveal the interior. Preferably, the macrodispersion is measured on a vulcanized elastomer composite. With regard to the macrodispersion, the term "particles" is intended to denote the area coverage of particle agglomerates, as distinguished from "primary particles", which form, for example, single carbon black agglomerates. Carbon black agglomerates have dimensions on the order of 0.1 μm scale, which is below the resolution of optical microscopy. This particle "size" associated with macro dispersion measurements is defined herein as the "area equivalent diameter" of the filler and is typically in the micron size range. Thus, the state of dispersion can be indicated by the form of the particle size distribution, whether by the area coverage of the particles or by the number of particles per unit area of a given size.
[0052] Alternatively, or in addition, when the filler comprises only carbon black and 10 to 100 wt. % (based on filler), for example 10 to 90 wt. %, 15 to 80 wt. %, 20 to 60 wt. %, or 30 to 50 wt. % recycled carbon, preferably wet-ground regenerated carbon, it may exhibit a macrodispersity of up to 1.9ln(x)+0.2, for example 1.9ln(x)-3.2 to 1.9ln(x)+0.2.
[0053] Exemplary types of elastomers include, but are not limited to, polymers (e.g., homopolymers, copolymers and / or terpolymers) of rubber, 1,3-butadiene, styrene, isoprene, isobutylene, 2,3-dialkyl-1,3-butadiene (wherein the alkyl can be methyl, ethyl, propyl, etc.), acrylonitrile, ethylene, propylene, etc. The elastomers may have a glass transition temperature (Tg) in the range of about -120°C to about 50°C as measured by differential scanning calorimetry (DSC). Examples include, but are not limited to, styrene-butadiene rubber (SBR), natural rubber and their functionalized derivatives, such as epoxidized and chlorinated rubber, polybutadiene rubber, polyisoprene rubber, ethylene-propylene copolymers (e.g., EPDM), isobutylene-based rubbers (e.g., butyl rubber), polychloroprene rubber, nitrile rubber, hydrogenated nitrile rubber, polyisoprene rubber, polysulfide rubber, polyacrylate elastomers, fluoroelastomers, perfluoroelastomers, and oil-extended derivatives of any of the foregoing. Blends and / or functionalized derivatives of any of the foregoing may also be used. Natural rubber may also be treated to chemically or enzymatically modify or reduce various non-rubber components.
[0054] Specific suitable synthetic rubbers include: copolymers of about 10 to about 70 weight percent styrene and about 90 to about 30 weight percent butadiene, such as a copolymer of 19 parts styrene and 81 parts butadiene, a copolymer of 30 parts styrene and 70 parts butadiene, a copolymer of 43 parts styrene and 57 parts butadiene, and a copolymer of 50 parts styrene and 50 parts butadiene; polymers and copolymers of conjugated dienes, such as polybutadiene, polyisoprene, polychloroprene, and the like, as well as polymers and copolymers of such conjugated dienes and copolymers thereof. and copolymers thereof with ethylene group-containing monomers copolymerizable therewith, such as styrene, methylstyrene, chlorostyrene, acrylonitrile, 2-vinyl-pyridine, 5-methyl-2-vinylpyridine, 5-ethyl-2-vinylpyridine, 2-methyl-5-vinylpyridine, allyl-substituted acrylates, vinyl ketones, methyl isopropenyl ketone, methyl vinyl ether, alpha-methylene carboxylic acids, and the like, and their esters and amides, such as acrylic acid and dialkylacrylic acid amides. Copolymers of ethylene with other higher alpha olefins, such as propylene, 1-butene, and 1-pentene, are also suitable for use herein.
[0055] The elastomer composite may further include additives to facilitate mixing, promote vulcanization, or impart specific properties to the vulcanizate of the elastomer composite. Numerous additives are known to those skilled in the art, including, for example, adhesion promoters, antioxidants, antiozonants, coupling agents, curing agents, antidegradants, plasticizers, processing aids (e.g., liquid polymers, oils, etc.), oil extenders, waxes, resins, flame retardants, extender oils, lubricants, tackifiers, vulcanization activators such as zinc oxide and fatty acids, vulcanization accelerators, and any mixtures thereof. Exemplary additives include, but are not limited to, zinc oxide and stearic acid. The general use and selection of such additives is known to those skilled in the art.
[0056] The dried pellets and / or spray dried pellets may be combined with an elastomer as described above using any dry mixing method known to those of skill in the art.
[0057] Alternatively, or in addition, the wet pellets may be combined with an elastomer according to one or more of the teachings of US Patent Publication No. 2022 / 0332016, WO 2021 / 247153, WO 2022 / 125679, WO 2022 / 125683, WO 2022 / 125677, and WO 2022 / 125675, the entire contents of all of which are incorporated herein by reference. For example, the wet pellets in solid form and the elastomer may be charged to a mixer and mixed under conditions where the temperature is controlled to remove at least a portion of the water in the pellets by evaporation. The elastomer is optionally premasticated prior to the introduction of the wet pellets. The wet filler may be added all at once or in aliquot portions.
[0058] Any suitable mixer, such as a Banbury or Brabender mixer, or other internal or closed mixer, or open mixer, or extruder or continuous mixer, or kneading mixer, or combinations thereof, can be used to combine the wet pellets with the elastomer. Other mixers include kneading type internal mixers. Commercially available internal mixers from Farrel-Pomini, Harburg Freudenberger Maschinenbau GmbH (HF), Kobelco, or Pelmar Eng'r Ltd can be used. As opposed to or in addition to the option of using an internal circuit of steam or water or other fluids in the rotor, the internal mixer can have a cooling or heating jacket in one area or part, or in two or more areas or parts of the mixing chamber, to control the temperature of the ingredients mixed therein. This allows one or more heating / cooling areas to be created in the wall or part of the wall of the mixer. The mixer can be a single stage mixer or a multi-stage mixer (e.g., two or more stages). Examples of mixers and designs that can be utilized are described in EP 2,423,253 and US Pat. No. 7,556,419, the disclosures of which are incorporated herein by reference.
[0059] Alternatively, the mixer can be a continuous mixer. For example, the solid elastomer and wet filler can be mechanically processed by using one or more of a continuous internal mixer, twin screw extruder, single screw extruder, or roll mill, as described in U.S. Pat. No. 9,855,686 (the disclosure of which is incorporated herein by reference). Suitable kneading and mastication devices are well known and commercially available, including, for example, the Unimix Continuous Mixer and MVX (mixing, degassing, extrusion) Machine from Farrel Pomini Corporation (Ansonia, Connecticut), the FCM™ Farrel Continuous Mixer from Pomini, Inc., long-shaft continuous mixer, Pomini continuous mixer, twin rotor co-rotating intermeshing extruder, twin rotor counter-rotating non-intermeshing extruder, continuous mixing extruder, twin screw kneading extruder manufactured by Kobe Steel, Ltd., and kobe continuous mixer. Alternative mastication devices suitable for use with one or more embodiments disclosed herein will be familiar to those skilled in the art.
[0060] The mixing can be carried out using a mixer having at least one rotor, which can be one or more of a kneader, a roll mill, a screw extruder, a twin screw extruder, a multi-screw extruder, a continuous mixer, and / or a twin screw extruder. The mixing can be carried out using a mixer having at least one rotor, which can have a two-blade rotor, a four-blade rotor, a six-blade rotor, an eight-blade rotor, and / or one or more screw rotors.
[0061] The mixing process for combining the wet pellets with the elastomer can be a one-stage (single stage) or multi-stage (multiple step) process. In a multi-stage process, one or more mixers or mixer types can be used. For stages in which an internal mixer is used, the fill rate in each such stage can be independently 72% or less, 70% or less, or 68% or less, or 66% or less, such as about 30%-72%, 40%-70%, 45%-70%, 30%-60%, 50-72%, 50-70%, 50-68%, 60-72%, 60-70%, 60-68%, 65-72%, 65-70%, 65-68%, or 40-60% or 50-60%, etc. The temperature of the mixer can be controlled to control the temperature of the mixture, the amount of water evaporated, or both. For example, in a multi-stage process, the temperature of the mixer for each stage can be controlled to control the amount of water evaporated from the mixture in the first mixing stage and one or more subsequent stages. For example, the liquid content of the discharged composite can be 10% to 99.9% (wt.% by wt.%), 10% to 95%, or 10% to 50% lower than the liquid content of the materials entering the mixer. Alternatively, or in addition, the rate of liquid release from the composite or mixture during mixing, e.g., due to evaporation, can be measured as the time-averaged release rate of liquid (e.g., total liquid removed / (release time x composite weight) per kg of composite or mixture, and this rate can be 0.01 to 0.14 kg / (min·kg) or 0.01 to 0.07 kg / (min·kg) or other rates less than or greater than this range.
[0062] Alternatively, or in addition, mixing may be controlled in one or more stages to provide a predetermined total specific energy (energy applied to the mixing system driving the one or more rotors per mass of composite, on a dry weight basis), for example between 1000 kJ / kg composite (or per kg of composite present in the mixer) and 10,000 kJ / kg composite (or per kg of composite present in the mixer), for example between 2,000 kJ / kg and 5,000 kJ / kg, or between 1,500 kJ / kg and 8,000 kj / kg, or between 1,500 kJ / kg and 7,000 kJ / kg. kJ / kg, 1,500 kJ / kg to 6,000 kJ / kg, 1,500 kJ / kg to 5,000 kJ / kg, 1,500 kJ / kg to 3,000 kJ / kg, 1,600 kJ / kg to 8,000 kJ / kg, 1,600 kJ / kg to 7,000 kJ / kg, 1,600 kJ / kg to 6,000 kJ / kg, 1,600 kJ / kg to 5,000 kJ / kg, 1,600 kJ / kg to 4,000 kJ / kg, 1,600 kJ / kg to 3,000 kJ / kg, or other values in any of these ranges. Alternatively, or in addition, the specific energy applied to the mixture may be split to ensure that a certain amount of specific energy is applied before or after a portion, for example, 75% of the filler, is added to the mixer. That is, the filler does not have to be added all at once. The mixing time in each stage may be any suitable time, for example, 1 minute to 40 minutes, 1 minute to 20 minutes, 1 minute to 15 minutes, 5 minutes to 30 minutes, 5 minutes to 20 minutes, 5 minutes to 15 minutes, or 1 minute to 12 minutes, 1 minute to 10 minutes, 3 minutes to 30 minutes, or other times. Alternatively, or in addition, the dump discharge temperature in each stage may be 120°C to 180°C, 120°C to 190°C, 130°C to 180°C, for example, 140°C to 180°C, 150°C to 180°C, 130°C to 170°C, 140°C to 170°C, 150°C to 170°C, etc., or other temperatures within or outside these ranges.
[0063] Following any one or more mixing steps or stages, the resulting composite may be subjected to one or more post-processing steps, for example, to mold or form the composite and / or to allow improved handling. Post-processing may provide a composite that can be dried, homogenized, extruded, calendared, ground, granulated, chopped, packaged, or sheeted. The composite may be compounded and vulcanized immediately or may be held for a period of time before compounding. Suitable equipment for the various post-processing steps includes, but is not limited to, one or more of an internal mixer, a kneader, a roll mill, an open mill, a screw extruder, a twin screw extruder, a multi-screw extruder, a continuous mixer, and / or a twin screw discharge extruder fitted with a roller die (e.g., a twin screw sheeter) or fitted with a stationary knife. Depending on which device is used, it may be desirable to process the composite through the device more than once, or through a series of similar or different devices having the same or different operating settings (e.g., speed, temperature, energy input, etc.). Alternatively, or in addition, the elastomer composite can be combined with added fillers, added elastomers, or both, prior to or as part of the vulcanization process. The additional fillers can be the same or different from the particulate fillers in the elastomer composite and can include any filler known to those skilled in the art, including those listed as additional and supplemental fillers, including additional wet regrind carbon. The added fillers and / or elastomers can increase or decrease the filler concentration of the vulcanizate relative to the elastomer composite.
[0064] To vulcanize the elastomer composite, the elastomer composite is combined with a curative package that includes a crosslinker, any necessary activators and accelerators, antioxidants, and any additional optional additives of those listed above. When sulfur is used as the crosslinker, typical activators include zinc oxide and / or stearic acid, and typical accelerators include sulfonamides such as N-tert-butyl-2-benzothiazole sulfenamide (TBBS) and N-cyclohexyl-2-benzothiazole sulfonamide (CBS). Antioxidants include N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine (6PPD) and those listed in WO 2012 / 037244. Other curatives used in rubber processing are peroxides, urethane crosslinkers, metal oxides, acetoxysilane mixtures, and the like. Additional suitable ingredients of sulfur-based and other crosslinking systems and methods of mixing and vulcanizing the elastomer composite are known to those skilled in the art. For example, typical techniques used in rubber compounding are described in Maurice Morto, Rubber Technology, 3rd Edition, Van Norstrand Reinhold Company, New York 1987, and 2nd Edition, Van Nordstrand Reinhold Company, New York 1973.
[0065] Various rubber articles may incorporate the vulcanizate. For example, the vulcanizate may be incorporated into a tire, such as a pneumatic tire, a non-pneumatic tire, or a solid tire. For example, the vulcanizate may be incorporated into a tire tread, a tire carcass, an undertread, an inner liner, a sidewall, a sidewall insert, a wire skim, or a cushion gum for a retread tire. Alternatively, or in addition, the vulcanizates may be incorporated into hoses, linings, liners, seals, gaskets, vibration isolation articles, trucks, track pads for truck propelled vehicle equipment, engine mounts, seismic stabilization devices, screens for mining equipment, linings for mining equipment, conveyor belts, chute liners, slurry pump liners, mud pump impellers, valve seats, valve bodies, piston hubs, piston rods, plungers, slurry mixing impellers and slurry pump impellers, grinder liners, cyclones and hydrocyclones, expansion joints, linings for dredge pumps and outboard pumps for marine equipment, shaft seals for marine, oil, space, and other applications, propeller shafts, or linings for pipes for transporting, for example, oil sands or tar sands. Alternatively, or in addition, the vulcanizates may be incorporated into engine mounts, bushings, weatherstripping, windshield wipers, automotive parts, seals, gaskets, housings, and wheel or truck elements.
[0066] The vulcanized elastomeric composite may exhibit a macrodispersion of up to 0.03x+4.4, e.g., 0.03x to 0.03x+4.4, where x is the fraction of recycled carbon in the particulate filler and the macrodispersion is the area fraction of undispersed filler particles greater than 5 μm as determined by optical microscopy in reflectance mode, especially when the filler comprises 10-100 wt.%, e.g., 10-90 wt.%, 15-80 wt.%, 20-60 wt.%, or 30-50 wt.% recycled carbon, preferably wet-ground regenerated carbon. Alternatively, or in addition, when the filler comprises only carbon black and 10-100 wt% (based on filler) recycled carbon, e.g., 10-90 wt%, 15-80 wt%, 20-60 wt%, or 30-50 wt% recycled carbon, preferably wet-ground regenerated carbon, the vulcanized elastomeric composite may exhibit a macrodispersity of up to 1.9ln(x)+0.2, e.g., 1.9ln(x)-3.2 to 1.9ln(x)+0.2. The resulting vulcanizate may have fatigue properties equal to or less than 10% of those of a vulcanizate made via the same process and composition, except with ASTM N550 carbon black instead of the recycled carbon. Alternatively, or in addition, the resulting vulcanizate may have fatigue properties equal to or greater than 90% of those of a vulcanizate made via the same process and composition, except with recycled carbon replaced by the same amount of additional filler used in the vulcanizate made according to the present invention.
[0067] The present invention is further clarified by the following examples, which are intended to be merely exemplary in nature. EXAMPLES
[0068] Example 1 Water (360 g) treated by reverse osmosis and 36 g of carbon sample (char from either CBP Cyprus or Polimix Ambiental Ltda, or Polimix 300 processed regenerated carbon from Polimix Ambiental Ltda) were charged to a half gallon ball mill containing a mixture of half inch (3320 g) and ¼ inch (2130 g) steel media. The mill was run continuously at 82 rpm for 6 hours under ambient conditions. The water and carbon mixture was removed from the mill and isolated from the grinding media. The char and processed regenerated carbon samples were also jet milled using a Jet Pulverizer Company 4 inch orbital Micron-Master jet mill. A vibratory feeder was used to feed the solid particles into an eductor filled with ambient air at 100 psi and into a chamber maintained at 40 psi.
[0069] Particle size distribution was evaluated on a Malvern Mastersizer 3000 instrument fitted with a HydroMV recirculation accessory. The HydroMV unit was filled with approximately 100 ml of deionized water. Water was recirculated through the detector window and a background measurement was taken to establish a baseline. A 0.02 g sample of dry powder (e.g., char or processed regenerated carbon) was combined with 50 ml of 1:3 (v:v) ethanol / water and 0.05% Triton® X100 dispersant. For wet samples and dispersions (e.g., wet regenerated carbon), the solids content of the dispersion was determined and enough material was added to the 1:3 ethanol / water mixture to make a dispersion of 0.02 g solids in 50 ml liquid with 0.05% Triton® X100 dispersant. For both wet and dry samples, the final mixture was probe sonicated for 10 minutes at 50% amplitude using a Branson 450D sonicator fitted with a 0.5 inch replaceable titanium tip probe. The freshly dispersed sample was added dropwise to the HydroMV unit until the obscuration level reached approximately 30%. Recirculation was continued for an additional 10 seconds before measurements were initiated. Instrument settings were as described in Table 1 below.
[0070] [Table 1]
[0071] The results are shown in Figures 1-3. Figure 1 shows the particle size distribution of raw char (CBP Cyprus), the raw char (dash-dotted line), the jet mill (dashed line), or the ball mill (solid line). Figure 2 shows the particle size distribution of ball milled samples of char (CBP Cyprus - dashed line - and Polimix Ambiental - dash-dotted line) and processed regenerated carbon (Polymix 300 - solid line). Figure 3 shows the particle size distribution of jet milled samples of char (CBP Cyprus - dashed line - and Polimix Ambiental - dash-dotted line) and Polymix 300 processed regenerated carbon (solid line). The results show that grinding in the presence of water provides a more efficient grinding with the maximum intensity of the distribution curve at particle sizes between 0.1 and 2 microns.
[0072] Example 2 1.1 kg of a ground slurry of wet reground carbon with a liquid / solid ratio of 10:1 (w / w) is poured into a 20 HP Feeco pin mixer charged with 1 kg of fluffy (unpelletized) N550 carbon black at ambient temperature. Mixing is continued at 1000 rpm for 90 seconds after which the pellets are discharged from the mixer. The resulting blended carbon pellets are then dried at 110° C. for 24 hours to achieve a moisture content of less than 1%. The dried pellets are then incorporated into a rubber formulation and compared to a reference N550 carbon black.
[0073] Example 3 Ball milling: Water treated by reverse osmosis and 36 g of commercial pyrolytic carbon (Technical Carbon Black, Reoil Sp.z oo, Myslenice, Poland) were charged to a half gallon ball mill containing a mixture of half inch (3320 g) and ¼ inch (2130 g) steel media. Sufficient water was used to produce either an 8.5 wt% (sample 1) or 20 wt% (samples 2, 3, 4, 5, and 6) mixture as shown in Table 2. The mill was operated continuously at 82 rpm for 24 hours under ambient conditions. The resulting mixture was removed from the mill and isolated from the grinding media to obtain a wet regrind carbon slurry. This process was repeated as necessary to obtain sufficient wet regrind carbon to produce rubbers as described below. A 25 wt% slurry was prepared in the same manner and had sufficient fluidity to be milled well.
[0074] Jet Milling: Comparative 1, 2, 3, 4, and 5 materials were prepared by jet milling commercial pyrolytic carbon (Technical Carbon Black, Reoil Sp.z oo, Myslenice, Poland) using a 4-inch orbit Micron-Master jet mill (Jet Pulverizer Company). A vibratory feeder was used to feed the solid particulates into an eductor filled with 80 psi ambient air and fed at approximately 60 g / min into a chamber maintained at 40 psi. ASTM N550 type carbon black (Sterling SO carbon black, Cabot Corporation) was jet milled in the same manner.
[0075] Pelletization: A 10 horsepower pin pelletizer was used with a loading of about 80%. For comparative samples 1, 2, 3, 4 and 5, jet milled commercial pyrolytic carbon (Technical Carbon Black, Reoil Sp.z oo, Myslenice, Poland) and jet milled ASTM N550 type carbon black were added to the pelletizer in the proportions shown in Table 2 and mixed at 1000 rpm for 15 seconds to obtain a homogenous blend of fluffy carbon. For comparative samples 2a and 5a, the jet milled ASTM N550 type carbon black was added to the pelletizer without blending. Water was then added to the pelletizer at a proportion of about 43% water by weight. For all comparative samples, the pelletizer was operated at 1000 rpm for 1 minute at ambient temperature. The resulting pellets were either used as is or dried to a moisture level of less than 1% by weight as shown in Table 2 below. The relative amount of regenerated carbon in the resulting pellets is shown in Table 2.
[0076] For samples 1-5, the appropriate amount of jet-milled carbon black (to give the percentage with wet regrind carbon shown in Table 2) was added to the pelletizer. The slurry resulting from ball milling (samples 1, 2, 3, 4, and 5) was then added to a pin pelletizer to make wet pellets with 52-62% water by weight. The relative amount of wet regrind carbon in the resulting pellets and the slurry concentration are shown in Table 2. For all samples, the pelletizer was operated at 1000 rpm for 1 minute at ambient temperature. The samples were either partially dried (to 43% moisture) or dried to a moisture level of less than 1% by weight, as shown in Table 2 below. The partially dried samples were placed in a 125°C oven with a sample depth of approximately 10 mm and checked periodically until the desired moisture level (43% by weight as a percentage of the total weight of wet filler) was reached. Pellet moisture was measured using a Mettler HE53 moisture analyzer (Mettler Toledo). Samples dried to a moisture level of less than 1% by weight were placed in a 125° C. oven with a sample depth of approximately 10 mm and left overnight.
[0077] Comparative Sample 6: Precipitated silica (348 g of Zeosil 1165MP silica from Solvay USA, Inc.) and commercial pyrolytic carbon (technical carbon black, Reoil Sp.z oo, Myslenice, Poland, used as is) were added to a 5 gallon plastic bucket to achieve a mixture with 26.9 wt. % pyrolytic carbon. Water was added to the particulate mixture to achieve a moisture level of 52.1 wt. % and the bucket was mixed on a roll mill for 30 minutes at 82 rpm to form pellets that were not further dried.
[0078] Sample 6: A 20 wt% slurry of precipitated silica (348 g of Zeosil 1165MP silica from Solvay USA, Inc.) and wet reground carbon was combined in a 5 gallon plastic bucket to make a mixture with 26.9 wt% (dry basis) wet reground carbon and a moisture level of 52.1%. The bucket was agitated on a roll mill for 30 minutes at 82 rpm to form pellets.
[0079] [Table 2]
[0080] Particle Size Distribution: The particle size distribution (PSD) of the reground carbon was measured using a scanning electron microscope. The PSD was measured for two separate aqueous slurries (listed as separate samples in Table 3 below) of each concentration of wet reground carbon (8.5% and 20%), an aqueous slurry of wet reground carbon and precipitated silica (sample 6), and jet-milled reground carbon. The relevant reground carbon samples were gently dispersed at a concentration of 0.2% by weight in water with 600 ppm Triton® X100 surfactant using a DISPERMAT disperser at 800 RPM for 5 minutes. The 0.2% by weight dispersion was then placed on a magnetic stir plate and mixed with a magnetic stir bar for 24 hours. The stirred dispersion was diluted to the appropriate concentration (0.4-4 ppm) using water with 600 ppm Triton® X100 for imaging by scanning electron microscopy (SEM). The diluted dispersion was vortex mixed at 3000 RPM for 30 seconds; then, 0.8 mL of the vortexed dispersion was placed on a 25 mm diameter polycarbonate membrane filter with 100 nm openings for filtration. The particles on the membrane filter were air-dried before SEM imaging.
[0081] The membrane filter was sputter coated with platinum to reduce charging during imaging. Two sets of SEM images were acquired using a Zeiss Ultra-plus field emission SEM with an SE2 detector at an electron acceleration voltage of 3 kv. The first set of 15 to 40 images were acquired with an image pixel size of 60 nm / pixel (×1500 magnification) in a field of view of 3072×2304 pixels, and the second set of 15 to 40 images were acquired with an image pixel size of 300 nm / pixel (×300 magnification) in a field of view of 3072×2304 pixels. Image locations on the membrane filter were randomly selected to encompass the entire filter surface area for a representative sampling of particles on the filter surface. Image analysis was performed using macros in NIH ImageJ software, and SEM images were processed to 1) minimize non-uniform image background using a pseudo flat-field correction method; 2) increase particle contrast using a local contrast enhancement method with locally adaptive histogram equalization in ImageJ; and 3) reduce image noise while preserving particle edges using a biexponential edge-preserving smoother in ImageJ. Local contrast differences at three different local region sizes were used to segment particles from the processed SEM images. Size and shape parameters for all particles in the segmented binary images were obtained from standard particle analysis methods in ImageJ. Depending on the width of the PSD, a total number of particles between 50,000 and 200,000 were imaged to achieve adequate accuracy. PSDs were generated by combining the PSD of submicron particles from a set of SEM images at 60 nm / pixel resolution with the PSD of particles 1 micron or larger from a set of SEM images at 300 nm / pixel resolution. To correct for the difference in total area for low-resolution and high-resolution images, each particle collected from the SEM image with a pixel size of 60 nm was counted with a number weighting factor equal to the ratio of the total number of particles larger than 1 micron in both the setting of the image with a pixel size of 300 nm and the setting of the image with a pixel size of 60 nm. To generate a continuous PSD from the list of discrete particle sizes, a B-spline interpolation algorithm was used to generate a smooth continuous cumulative particle size distribution, and then a probability density distribution was calculated based on the first derivative of the cumulative distribution using a noise-resistant smooth differentiator.The area equivalent circular diameter Dcirc (equivalent to twice the square root of the projected area in the image divided by π) was used as a measure of particle size. The volume weighting of the particles is based on the volume of the particle estimated from the area and perimeter of the particle in the SEM image using the formula in ASTM D3849. The volume weighted particle size distribution is shown in Table 3. The wet-ground regrind carbon shows a smaller particle size distribution and fewer particles above 2 and 5 microns than the jet-ground regrind carbon.
[0082] [Table 3]
[0083] Rubber mixes: Rubbers with a particulate concentration of 50 phr were prepared using the smalls and curatives shown in Table 4, and the amounts of SMR20 natural rubber, Buna CB24 butadiene rubber (Lanxess), or Kralex SBR 1502 styrene butadiene rubber (Synthos) listed in Table 5 below. In addition, two samples were prepared by dry mixing with 100 phr of natural rubber (SMR20 grade) using 50 phr of Sterling SO carbon black (Comparative 7) or commercial pyrolytic carbon (Comparative 8, technical carbon black, Reoil Sp.z oo, Myslenice, Poland). All compositions were mixed in a 439 mL Brabender Prep-Mixer with two cam rotors. Dry mix samples (less than 1 wt.% pellet moisture) were prepared in two stages as described in Table 6, and wet mix samples (greater than 1 wt.% pellet moisture) were prepared in three stages as described in Table 7. Regardless of which method was used, after each mixing stage the mixture was sheeted on a two-roll mill operated at 50°C and approximately 22 rpm, followed by banding for 60 seconds, six passes with a nip gap of approximately 5 mm, and a rest period of at least 3 hours before the next stage of mixing (or curing, after the last stage). Curing was carried out in a heated press (150°C, 2500 lbs) for a time of T90+10% of T90 (where T90 is the time to achieve 90% vulcanization) as determined by a conventional rubber rheometer.
[0084] [Table 4] a) For use in silica-containing formulations only; HB Chemical's Bis[3-(triethoxysilyl)propyl] polysulfide b) 2 phr for pellets with less than 1% moisture by weight, otherwise 2.5 phr; N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine, standard 6PPD (Harwick Standard) c) Poly(1,2-dihydro-2,2,4-trimethyl-quinoline), antioxidant DQ pellets (Akrochem Corporation) d) Akrochem Corporation e)AKROWAXTM 5031(Akrochem Corporation) f) N-tert-butyl-2 benzothiazole sulfenamide (Akrochem Corporation)
[0085] [Table 5]
[0086] [Table 6]
[0087] [Table 7]
[0088] The following tests were used to obtain performance data for each vulcanizate. Tensile stress at 100% elongation (M100) and 300% elongation (M300) were evaluated according to ASTM D412 (Test Method A, Type C) at 23°C, 50% relative humidity, and a crosshead speed of 500 mm / min. Tensile strain was measured using an extensometer. The ratio of M300 / M100 is called the tensile stress ratio (or modulus ratio). Type B tear strength of the cured rubber samples is measured at 23°C according to ATSM D624. Cured samples were cut with a guillotine to prepare them for macrodispersion analysis. Images were digitally captured using an Idea 5Mp color mosaic camera and Spot imaging software, version 5.6.11 (Spot Imaging, Sterling Heights, MI) in conjunction with an Olympus BH-2 microscope (using a ring light as the illumination source in reflectance mode). The overall magnification of the captured images was 100x. Picassa (Google) was used to enhance the contrast of particles against the background. NIH ImageJ software was used to identify and quantitate weak aggregates using the default settings of the autothreshold method and appropriate background leveling (set via background subtraction ball radius) as well as an erosion loop to distinguish knife marks, which tend to have a circularity of less than 0.3, from weak aggregates (circularity of 0.3 or greater). ImageJ software was used to extract binary images (area equivalent diameter = (4 * area of dark object / π) 1 / 2 ) was defined as the area equivalent diameter of the corresponding object. Three images of randomly selected areas of the sample were measured for each sample, and agglomerates with a diameter of at least 5 microns were considered "undispersed."
[0089] The vulcanizate properties are listed in Table 8 below. The results show that the reduced proportion of large agglomerates in the wet regrind carbon of the examples correlates with reduced undispersed area and improved modulus ratios and tear strength for elastomer composite vulcanizates with a greater proportion of such agglomerates. The results are shown in Figure 4. The triangles represent comparative samples and the circles represent samples prepared according to embodiments of the present invention.
[0090] [Table 8]
[0091] Example 4 Water treated by reverse osmosis and 36 g of commercially available pyrolytic carbon (Technical Carbon Black, Reoil Sp.z oo, Myslenice, Poland) are charged to a half gallon ball mill containing a mixture of half inch (3320 g) and ¼ inch (2130 g) steel media. Sufficient water is added to produce a 25% by weight mixture. The mill is operated continuously at 82 rpm for 24 hours under ambient conditions. The resulting mixture is removed from the mill and isolated from the grinding media to yield a slurry of wet reground carbon having a d50 of 2700 nm or less and 15% or less particles with a diameter greater than 5 microns, as measured using the SEM method outlined above. The slurry is distilled to remove water until the solids content is about 65-70%, and then the partially dried slurry is dried in an oven at 125°C until the moisture content is about 40-50%. The resulting wet filler is pelletized as described above. The resulting pellets are either used as is without drying or are dried to a moisture content of less than 1% and combined with an elastomer to form an elastomer composite.
[0092] The foregoing description of preferred embodiments of the present invention has been presented for purposes of illustration and description. It is not intended to be exhaustive or to limit the invention to the precise form disclosed. Modifications and variations are possible in light of the above teachings or may be acquired from practice of the invention. The embodiments have been chosen and described in order to explain the principles of the invention and its practical application, and to enable those skilled in the art to utilize the invention in various embodiments, in various aspects, and with various modifications, as suited to the particular use contemplated. It is intended that the scope of the present invention be defined by the claims appended hereto and their equivalents.
Claims
1. 1. A method for treating particulate carbon comprising: combining pyrolytic carbon with water to form a mixture to form an initial slurry having a solids content of 1-35% by weight; and 16. The method of claim 15, further comprising: grinding the pyrolytic carbon to form a grind slurry comprising wet regrind carbon and water; and wherein a volume weighted particle size distribution of the wet regrind carbon as measured via scanning electron microscopy has one or more of a D50 of 2700 nm or less and 15% or less of particles having a particle size greater than 5 microns.
2. 2. The method of claim 1, wherein D50 is from 1000 nm to 2700 nm, for example from 1200 nm to 2500 nm.
3. 3. The method according to claim 1 or 2, wherein D75 is from 2500 nm to 3300 nm, for example from 1700 nm to 3000 nm.
4. A method according to any one of claims 1 to 3, wherein between 3% and 10% of the wet regrind carbon particles have a particle size greater than 5 microns.
5. A method according to any preceding claim, wherein up to 65% of the wet regrind carbon particles have a particle size greater than 2 microns, for example 25-60%.
6. The method of any one of claims 1 to 5, further comprising removing contaminants visible to the naked eye from the initial slurry.
7. The method according to any one of claims 1 to 6, wherein the initial slurry has a solids content of up to 25% by weight.
8. The method of any one of claims 1 to 7, wherein said combining further comprises combining at least one auxiliary filler with said water to form said initial slurry.
9. 9. The method of claim 8, wherein the auxiliary filler is selected from the group consisting of carbon black, silicon treated carbon black, silica coated carbon black, precipitated silica, hydrothermal carbon, artificial polysaccharides, graphene, graphene oxide, reduced graphene oxide, nanocellulose, lignin, clay, nanoclay, metal oxides, metal carbonates, single walled carbon nanotubes, multi walled carbon nanotubes, carbon nanostructures, carbon black coated particles, and mixtures of two or more thereof.
10. The method according to any one of claims 1 to 9, wherein the milling is carried out using at least one device selected from a cutter mixer, a ball mill, a media mill, a homogenizer, an attritor, a horizontal bead mill, a rotor stator mill, and a colloid mill.
11. 11. The method of any one of claims 1 to 10, further comprising adding at least one additional filler selected from carbon black, silicon treated carbon black, silica coated carbon black, carbon black coated particles, and precipitated silica to the ground slurry to provide a solids content of the resulting wet blended carbon mixture of 25 to 70 weight percent.
12. 12. The method of claim 11, wherein said adding comprises adding an aqueous slurry comprising said at least one additional filler.
13. 13. The method of claim 11 or 12, further comprising densifying the wet blended carbon mixture.
14. The method of claim 13 , wherein the densifying comprises pelletizing the wet blend carbon mixture to form pellets or spray drying the wet blend carbon mixture.
15. The method of claim 14 further comprising drying the pellets.
16. the water being a continuous flow of water; the milled slurry being a continuous flow of the milled slurry; said combining includes metering said pyrolytic carbon into said continuous stream of water; The method according to any one of claims 1 to 15.
17. 17. The method of claim 16, wherein said combining further comprises metering at least one auxiliary filler into said continuous stream of water.
18. 18. The method of claim 17, wherein the auxiliary filler is selected from the group consisting of carbon black, silicon treated carbon black, silica coated carbon black, precipitated silica, hydrothermal carbon, artificial polysaccharides, graphene, graphene oxide, reduced graphene oxide, nanocellulose, lignin, clay, nanoclay, metal oxides, metal carbonates, single walled carbon nanotubes, multi walled carbon nanotubes, carbon nanostructures, carbon black coated particles, and mixtures of two or more thereof.
19. 19. The method of any one of claims 16 to 18, further comprising metering at least one additional filler selected from carbon black, silicon treated carbon black, silica coated carbon black, carbon black coated particles, and precipitated silica into said continuous stream of ground slurry to provide a solids content of the resulting continuous stream of wet blended carbon mixture of from 25 to 70 weight percent.
20. 20. The method of claim 19, wherein said metering comprises metering an aqueous slurry of said additional filler into said continuous stream of said ground slurry.
21. The method of any one of claims 16 to 20, further comprising granulating the wet blended carbon mixture.
22. 22. The method of claim 21, wherein the granulating comprises pelletizing the wet blended carbon mixture to form pellets or spray drying the wet blended carbon mixture.
23. 23. The method of claim 22, further comprising drying the pellets.
24. The method of any one of claims 1 to 23, further comprising granulating the solids in the milled slurry.
25. 25. The method of claim 24, wherein the granulating comprises spray drying the milled slurry or pelletizing the solids in the milled slurry.
26. Pellets produced by the method according to any one of claims 1 to 25.
27. 1. A particulate filler comprising at least 10% by weight (dry basis) of recycled carbon, wherein a volume weighted particle size distribution of said recycled carbon as measured via scanning electron microscopy has one or more of a D50 of 2700 nm or less and 15% or less of particles having a particle size greater than 5 microns.
28. 28. The particulate filler of claim 27, wherein D50 is from 1000 nm to 2700 nm, for example from 1200 nm to 2500 nm.
29. 29. A particulate filler according to claim 27 or 28, wherein D75 is from 2500 nm to 3300 nm, for example from 1700 nm to 3000 nm.
30. A particulate filler according to any one of claims 27 to 29, wherein between 3% and 10% of the recycled carbon particles have a particle size greater than 5 microns.
31. A particulate filler according to any one of claims 27 to 30, wherein up to 65% of the recycled carbon particles have a particle size greater than 2 microns, for example 25 to 60%.
32. 32. A particulate filler according to any one of claims 27 to 31, wherein the particulate filler comprises 10 to 100%, 10 to 90%, 15 to 80%, 20 to 60%, or 30 to 50% by weight of recycled carbon.
33. 33. The particulate filler of any one of claims 27 to 32, further comprising one or more auxiliary fillers selected from carbon black, silicon treated carbon black, silica coated carbon black, precipitated silica, hydrothermal carbon, artificial polysaccharides, graphene, graphene oxide, reduced graphene oxide, nanocellulose, lignin, clay, nanoclay, metal oxides, metal carbonates, single walled carbon nanotubes, multi walled carbon nanotubes, carbon nanostructures and carbon black coated particles.
34. Particulate filler according to any one of claims 27 to 33, wherein the particulate filler has a moisture content of 15 to 80% by weight, such as 40 to 60% by weight.
35. A particulate filler according to any one of claims 27 to 34, wherein the particulate filler is in the form of pellets.
36. A particulate filler according to claim 33, wherein the pellets have a moisture content of from 15 to 80% by weight, such as from 40 to 60% by weight.
37. 35. The particulate filler of claim 34, wherein the pellets contain 3% or less water.
38. A particulate filler according to any one of claims 35 to 37, wherein the pellet consists essentially of the particulate filler, optional water, and optional binder.
39. 39. A pellet comprising the particulate filler of any one of claims 27 to 38 and further comprising at least one additional filler selected from carbon black, silicon treated carbon black, silica coated carbon black, carbon black coated particles, and precipitated silica.
40. A particulate filler according to any one of claims 27 to 39, wherein the regenerated carbon is wet-ground regenerated carbon.
41. 1. An elastomer composite comprising a mixture of an elastomer and 30 to 90 phr of a particulate filler, the particulate filler comprising at least 10 wt. % recycled carbon having one or more of a D50 (volume weighted) of 2700 nm or less and 15% (volume weighted) or less of particles having a particle size greater than 5 microns as measured by scanning electron microscopy.
42. 42. The elastomer composite of claim 41, wherein the particulate filler comprises 10-100%, 10-90%, 15-80%, 20-60%, or 30-50% by weight recycled carbon.
43. 43. The elastomer composite of claim 41 or 42, wherein D50 is from 1000 nm to 2700 nm, for example from 1200 nm to 2500 nm.
44. 44. The elastomer composite of claim 41, wherein D75 is from 2500 nm to 3300 nm, for example from 1700 nm to 3000 nm.
45. 45. The elastomer composite of any one of claims 41 to 44, wherein between 3% and 10% of the recycled carbon particles have a particle size greater than 5 microns.
46. A particulate filler according to any one of claims 41 to 45, wherein up to 65% of the recycled particles, for example 25 to 60%, have a particle size above 2 microns.
47. 47. The elastomer composite of any one of claims 41 to 46, wherein the particulate filler is present in an amount of 30 to 70 phr, such as 35 to 60 phr or 40 to 55 phr.
48. 48. The elastomer composite of any one of claims 41 to 47, wherein the elastomer composite exhibits a macrodispersion of up to 0.03x + 4.4, where x is the percentage of recycled carbon in the particulate filler, and the macrodispersion is the area percentage of undispersed filler particles greater than 5 μm as determined by optical microscopy in reflectance mode.
49. 49. The elastomer composite of any one of claims 41 to 48, wherein the elastomer composite exhibits a macrodispersion of from 0.03x to 0.03x + 4.4, where x is the percentage of recycled carbon in the particulate filler, and the macrodispersion is the area percentage of undispersed filler particles greater than 5 μm as determined by optical microscopy in reflectance mode.
50. 50. The elastomer composite of any one of claims 41 to 49, wherein the particulate filler further comprises one or more of carbon black, silicon treated carbon black, silica coated carbon black, precipitated silica, hydrothermal carbon, artificial polysaccharides, graphene, graphene oxide, reduced graphene oxide, nanocellulose, lignin, clay, nanoclay, metal oxides, metal carbonates, single walled carbon nanotubes, multi walled carbon nanotubes, carbon nanostructures, and carbon black coated particles.
51. 51. The elastomer composite of any one of claims 41-50, wherein the particulate fillers are recycled carbon and carbon black, and the elastomer composite exhibits a macrodispersion of up to 1.9ln(x)+1.2, where x is the percentage of recycled carbon in the particulate filler, and the macrodispersion is the area percentage of undispersed filler particles greater than 5 μm as determined by optical microscopy in reflectance mode.
52. 52. The elastomer composite of claims 41-51, wherein the particulate fillers are recycled carbon and carbon black, and the elastomer composite exhibits a macrodispersion of from 1.9ln(x)-3.2 to 1.9ln(x)+0.2, where x is the percentage of recycled carbon in the particulate filler, and the macrodispersion is the area percentage of undispersed filler particles greater than 5 μm as determined by optical microscopy in reflectance mode.
53. 53. The elastomer composite of any one of claims 41 to 52, wherein the elastomer is selected from natural rubber, functionalized natural rubber, styrene-butadiene rubber, functionalized styrene-butadiene rubber, polybutadiene rubber, functionalized polybutadiene rubber, polyisoprene rubber, ethylene-propylene copolymers, isobutylene based rubber, polychloroprene rubber, nitrile rubber, hydrogenated nitrile rubber, polysulfide rubber, polyacrylate elastomers, fluoroelastomers, perfluoroelastomers, and blends thereof.
54. 54. The elastomer composite of any one of claims 41 to 53, wherein the recycled carbon is wet-ground reclaimed carbon.
55. The elastomeric composite of any one of claims 41 to 54, wherein the elastomeric composite is a vulcanized elastomeric composite.
56. A tire tread comprising a vulcanizate of a mixture comprising the elastomer composite of any one of claims 41 to 54 and a curative package.
57. 55. An article comprising a vulcanizate of a mixture comprising the elastomer composite of any one of claims 41 to 54 and a curative package.
58. 58. The article of claim 57, wherein the article is incorporated into a pneumatic tire, a non-pneumatic tire, or a solid tire.
59. 60. The article of claim 57 or 58, wherein the article is selected from tire treads, undertreads, innerliners, sidewalls, sidewall inserts, wire skims, and cushion gums for retreaded tires.
60. 58. The article of claim 57, wherein the article is selected from hoses, linings, liners, seals, gaskets, vibration isolation articles, trucks, track pads for truck propelled vehicle equipment, engine mounts, seismic stabilization devices, screens for mining equipment, linings for mining equipment, conveyor belts, chute liners, slurry pump liners, mud pump impellers, valve seats, valve bodies, piston hubs, piston rods, plungers, slurry mixing impellers and slurry pump impellers, grinder liners, cyclones and hydrocyclones, expansion joints, linings for dredge pumps and outboard pumps for marine equipment, shaft seals for marine, oil, aerospace, and other applications, propeller shafts, pipe linings, engine mounts, bushings, weatherstripping, windshield wipers, automotive parts, seals, gaskets, housings, wheel elements, and truck elements.
61. 55. A vulcanizate of a mixture comprising the elastomer composite of any one of claims 41 to 54 and a curative package, said vulcanizate having fatigue properties equivalent to or at least 90% of a vulcanizate produced via the same process and same composition except having ASTM N550 carbon black instead of the recycled carbon.
62. 55. A vulcanizate of a mixture comprising the elastomer composite of any one of claims 41 to 54 and a curative package, said vulcanizate exhibiting a macrodispersion of up to 0.03x+4.4, where x is the percentage of recycled carbon in the particulate filler, and where the macrodispersion is the area percentage of undispersed filler particles greater than 5 μm as determined by optical microscopy in reflectance mode.
63. 55. A vulcanizate of a mixture comprising the elastomer composite of any one of claims 41 to 54 and a curative package, said vulcanizate exhibiting a macrodispersion of from 0.03x to 0.03x + 4.4, where x is the percentage of recycled carbon in the particulate filler, and where the macrodispersion is the area percentage of undispersed filler particles greater than 5 μm as determined by optical microscopy in reflectance mode.
64. 55. A vulcanizate of a mixture comprising the elastomer composite of any one of claims 41 to 54 and a curative package, wherein the particulate fillers are recycled carbon and carbon black, and the vulcanizate exhibits a macrodispersion of up to 1.9ln(x)+0.2, where x is the percentage of recycled carbon in the particulate filler, and the macrodispersion is the area percentage of undispersed filler particles greater than 5 μm as determined by optical microscopy in reflectance mode.
65. 55. A vulcanizate of a mixture comprising the elastomer composite of any one of claims 41 to 54 and a curative package, wherein the particulate fillers are recycled carbon and carbon black, and the elastomer composite exhibits a macrodispersion of from 1.9ln(x)-3.2 to 1.9ln(x)+0.2, where x is the percentage of recycled carbon in the particulate filler, and the macrodispersion is the area percentage of undispersed filler particles greater than 5 μm as determined by optical microscopy in reflectance mode.
66. 1. An elastomer composite comprising a mixture of an elastomer and 30-90 phr of a particulate filler, the particulate filler comprising at least 10 wt. % recycled carbon, the elastomer composite exhibiting a macrodispersion of at most 0.03x+4.4, where x is the percentage of recycled carbon in the particulate filler, and the macrodispersion is the area percentage of undispersed filler particles greater than 5 μm as determined by optical microscopy in reflectance mode.
67. 67. The elastomer composite of claim 66, wherein the elastomer composite exhibits a macrodispersion from 0.03x to 0.03x + 4.4, where x is the percentage of recycled carbon in the particulate filler, and the macrodispersion is the area percentage of undispersed filler particles greater than 5 μm as determined by optical microscopy in reflectance mode.
68. 1. An elastomer composite comprising a mixture of an elastomer and 30 to 90 phr of a particulate filler, the particulate filler comprising at least 10 wt. % recycled carbon with the balance being the carbon black, the elastomer composite exhibiting a macrodispersion of up to 1.9ln(x)+1.2, where x is the percentage of recycled carbon in the particulate filler and the macrodispersion is the area percentage of undispersed filler particles greater than 5 μm as determined by optical microscopy in reflectance mode.
69. 69. The elastomer composite of claim 68, wherein the elastomer composite exhibits a macrodispersion of from 1.9ln(x)-3.2 to 1.9ln(x)+0.2, where x is the percentage of recycled carbon in the particulate filler, and the macrodispersion is the area percentage of undispersed filler particles greater than 5 μm as determined by optical microscopy in reflectance mode.
70. 70. The elastomeric composite of any one of claims 66 to 69, wherein the elastomeric composite is vulcanized.
71. 71. The elastomer composite of any one of claims 66 to 70, wherein the recycled carbon is wet-ground reclaimed carbon.
72. 72. The elastomer composite of any one of claims 66-71, wherein the recycled carbon has one or more of a D50 (volume weighted) of 2700 nm or less and 15% (volume weighted) or less of particles having a particle size greater than 5 microns as measured by scanning electron microscopy.
Citation Information
Patent Citations
Method for manufacturing mixture
CN107406596A
Preparation of raw rubber having improved reinforceability containing thermal decomposition residue of waste tire
JP1977037950A
Pouring apparatus for ALC raw material slurry
JP1995276343A
Make up cosmetic
JP1996301727A
Production of rubber composition containing modified carbon black for rubber reinforcement
JP1999049895A
Cited By
Accelerated encoding for virtual machine synchronization
US12474948B2